Development and characterization of three cell culture systems to investigate the relationship between primary bone marrow adipocytes and myeloma cells - Fairfield, Heather; Condruti, Rebecca; Farrell, Mariah; Di Iorio, Reagan; Gartner, Carlos A.; Vary, Calvin; Reagan, Michaela R. (Frontiers in Oncology, 2023)
The unique properties of the bone marrow (BM) allow for migration and proliferation of multiple myeloma (MM) cells while also providing the perfect environment for development of quiescent, drug-resistant MM cell clones. BM adipocytes (BMAds) have recently been identified as important contributors to systemic adipokine levels, bone strength, hematopoiesis, and progression of metastatic and primary BM cancers, such as MM. Recent studies in myeloma suggest that BMAds can be reprogrammed by tumor cells to contribute to myeloma-induced bone disease, and, reciprocally, BMAds support MM cells in vitro. Importantly, most data investigating BMAds have been generated using adipocytes generated by differentiating BM-derived mesenchymal stromal cells (BMSCs) into adipocytes in vitro using adipogenic media, due to the extreme technical challenges associated with isolating and culturing primary adipocytes. However, if studies could be performed with primary adipocytes, then they likely will recapitulate in vivo biology better than BMSC-derived adipocytes, as the differentiation process is artificial and differs from in vivo differentiation, and progenitor cell(s) of the primary BMAd (pBMAds) may not be the same as the BMSCs precursors used for adipogenic differentiation in vitro. Therefore, we developed and refined three methods for culturing pBMAds: two-dimensional (2D) coverslips, 2D transwells, and three-dimensional (3D) silk scaffolds, all of which can be cultured alone or with MM cells to investigate bidirectional tumor-host signaling. To develop an in vitro model with a tissue-like structure to mimic the BM microenvironment, we developed the first 3D, tissue engineered model utilizing pBMAds derived from human BM. We found that pBMAds, which are extremely fragile, can be isolated and stably cultured in 2D for 10 days and in 3D for up to 4 week in vitro. To investigate the relationship between pBMAds and myeloma, MM cells can be added to investigate physical relationships through confocal imaging and soluble signaling molecules via mass spectrometry. In summary, we developed three in vitro cell culture systems to study pBMAds and myeloma cells, which could be adapted to investigate many diseases and biological processes involving the BM, including other bone-homing tumor types.